2017
DOI: 10.1021/jacs.6b13020
|View full text |Cite
|
Sign up to set email alerts
|

A Liquid-Crystalline Phenylene-Based Shape-Persistent Molecular Spoked Wheel

Abstract: Molecular spoked wheels with an all-phenylene backbone and different alkoxy side chain substitution patterns were synthesized using a cobalt-catalyzed [2 + 2 + 2] cycloaddition and subsequent template-directed cyclization via Yamamoto coupling. The two-dimensional organization of the molecules at the solid/liquid interface was investigated by means of scanning tunneling microscopy, allowing imaging of the molecular structure with submolecular resolution. With the right proportion of the flexible alkyl corona t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Transition‐metal catalyzed cross‐coupling reactions are nowadays of paramount importance in the synthetic chemist's toolbox for the formation of carbon‐carbon and carbon‐heteroatom bonds . In modern organometallic chemistry, the Sonogashira‐Hagihara (SH) reaction is among the only cross‐coupling useful for constructing new carbon‐carbon bonds between terminal alkyne motifs and aryl or vinyl halides(pseudohalides) to generate various conjugated enynes of interest in the pharmaceutical industry, in material sciences, and for the total synthesis of natural products . The use of a Cu(I) halide salt as co‐catalyst generally increases the reactivity of the reagents and allows the reaction to proceed under mild reaction conditions .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition‐metal catalyzed cross‐coupling reactions are nowadays of paramount importance in the synthetic chemist's toolbox for the formation of carbon‐carbon and carbon‐heteroatom bonds . In modern organometallic chemistry, the Sonogashira‐Hagihara (SH) reaction is among the only cross‐coupling useful for constructing new carbon‐carbon bonds between terminal alkyne motifs and aryl or vinyl halides(pseudohalides) to generate various conjugated enynes of interest in the pharmaceutical industry, in material sciences, and for the total synthesis of natural products . The use of a Cu(I) halide salt as co‐catalyst generally increases the reactivity of the reagents and allows the reaction to proceed under mild reaction conditions .…”
Section: Methodsmentioning
confidence: 99%
“…[1,2] In modern organometallic chemistry, the Sonogashira-Hagihara (SH) reaction is among the only crosscoupling useful for constructing new carbon-carbon bonds between terminal alkyne motifs and aryl or vinyl halides (pseudohalides) to generate various conjugated enynes of interest in the pharmaceutical industry, in material sciences, and for the total synthesis of natural products. [3][4][5][6][7] The use of a Cu(I) halide salt as co-catalyst generally increases the reactivity of the reagents and allows the reaction to proceed under mild reaction conditions. [1,2] At the same time, however, the presence of copper can result in the formation of undesired alkyne dimers (homocoupling products) upon oxidation (Glaser coupling).…”
mentioning
confidence: 99%
“…However, it was found that the spoked wheels based on poly(p-phenylene ethynylene)s decomposed slowly at room temperature. 132 In order to increase the stability of the spoked wheels, another synthetic strategy was established by Müllen and Höger independently in recent years. 25,132 The new type of spoked wheels were build up based on poly(p-phenylene)s instead of poly(p-phenylene ethynylene)s with the purpose for enhancing the stability and rigidity.…”
Section: Spoked Wheelsmentioning
confidence: 99%
“…132 In order to increase the stability of the spoked wheels, another synthetic strategy was established by Müllen and Höger independently in recent years. 25,132 The new type of spoked wheels were build up based on poly(p-phenylene)s instead of poly(p-phenylene ethynylene)s with the purpose for enhancing the stability and rigidity. In contrast to the previous synthesis (Figure 10), the spoke 36 was attached onto the key backbone 35 directly through Suzuki coupling on Ph C with one acetylene in the center.…”
Section: Spoked Wheelsmentioning
confidence: 99%
“…21,32 PAHs larger than HBC, as well as non-planar bowl-shaped PAHs, such as corannulene and sumanene were demonstrated to be also applicable as discotic LC materials. 23,[39][40][41][42] Nevertheless, the LC behaviours of PAHs other than triphenylenes, HBCs and perylenes are still underexplored and there is so far only a limited number of PAHs that are known to show LC properties. In particular, LC PAHs with smaller HOMO-LUMO gaps are seldom reported, despite the interest in their longer-wavelength absorption and emission as well as potential to achieve higher charge-carrier mobilities.…”
Section: Introductionmentioning
confidence: 99%